Implementation of Augmented Reality-Based Learning Media on The Material of Grouping Animals Based on Their Food Types for Class III Students - Rossa Ilma Silviah; Novaria Jannah; Lailatul Mufidah (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study aims to test the results of the development of Augmented Reality-based learning media using the Assmblr Edu platform on the material of grouping animals based on their food types, namely herbivores, carnivores, and omnivores, for third-grade elementary school students. The background of this study is based on the low interest of students in learning science material due to the limited learning media that can provide an interesting and enjoyable learning experience. The development model used in this study is the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study consisted of 16 third-grade students of SDN Kedensari 1. The instruments used included validation by material experts and media experts, teacher response questionnaires, student response questionnaires, and student evaluation tests. The results of this validation indicate that the AR-based learning media developed is included in the category of very valid and feasible to use. In addition, this media also received positive responses from teachers and was proven to improv